LEGAL CONSEQUENCES OF THE CONSCRIPTION OF THE POPULATION INTO COMPULSORY LABOUR IN THE TURKESTAN GENERAL GOVERNORATE - Ulug'bek Qo'chqorovich Ismoilov; Muqimjon Qirg'izboyev (International Journal of Literature and Language Studies, 2026)
Abstract: This article analyses, on the basis of a historical-legal methodology, the legal consequences of the conscription of the indigenous population into various forms of compulsory labour during the period of the Turkestan General Governorate (1867–1917). In particular, sustained attention is devoted to the damage inflicted upon the personal and property rights of the population, the changes occurring in communal-corporative legal relations, the genuine or illusory nature of judicial and administrative protection mechanisms, and the influence of labour obligations upon the subsequent socio-legal incapacitation of the population.